MULTIMEDIA CREATIVE PROJECT AS AN INNOVATIVE EDUCATIONAL TECHNOLOGY - Yanenko, Yaroslav (Educological discourse, 2020)
The article is devoted to the definition of the features of multimedia creative projects as innovative educational technology. As a result of the study, the main components of modern multimedia creative projects, in particular, graphic layouts, were identified; materials for social networks; site projects; text materials intended for distribution in modern media, etc. The article clarifies the possibilities of introducing multimedia creative projects into the process of blended learning for students. Multimedia creative projects is one of the ways to solve the problem of efficient use of time allotted in the disciplines for independent work of students and its effective combination with lectures and practical exercises. Multimedia creative projects can act as additional tools for modular and semester control. Public protection of multimedia creative projects is an effective way to test students' knowledge and skills. Specialists of the local media market and heads of media departments of Sumy State University take part in open defense by students of multimedia creative projects. This allows students to effectively present themselves to potential employers. The article notes the relationship of multimedia creative projects with classroom activities and features of the use of multimedia technologies in creative projects. Multimedia creative projects complement lectures and practical exercises in the sense of building professional competencies for future specialists and allow students to focus on specific topics or questions of the course. The article clarifies the role of multimedia creative projects in the training of future specialists, in particular, this is the application by students of theoretical knowledge in practice, it is the acquisition by them of new practical skills in the chosen field, this impact on the formation of professional student portfolios that can be used in the search for future work. When creating creative projects, students use various multimedia technologies. These technologies allow future professionals to develop messages designed for distribution in modern media.